Application and assessment of rockall scoring system in managmenet of patients with upper gastrointestinal bleeding in prediction of mortality and rebleeding - Mahmoud Mohamed Essame Eldeen; Hazem Hossam; Helmy Elghawaby; Mohsen Salama (Cairo : Mahmoud Mohamed Essame Eldeen, 2010)
Acute upper gastrointestinal bleeding is a relatively common potentially life - threatening medical emergency that necessitate I.C.U admission , scoring system help risk stratification and prediction of mortality and re - bleeding in those patient . The study done to apply and asses validity of Rackall scoring system in prediction of mortality and re - bleeding in patient with acute UGIB
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Critical Care Medicine
Issued also as CD
Keywords: Intesive care units; Rockall scoring system; Upper gastrointestinal bleeding